Public law - Monaghan, Chris (UK, Routledge, 2022)
"Public Law guides students through all the essential components of the Public Law module, in a user-friendly structure that is ideal for visual learners. Written by an experienced teacher of Public Law, the book takes an accessible and engaging approach to often complex areas of law, politics and the constitution. Incorporating recent developments, academic debate and commentary, the book introduces students to all the key concepts of this core subject. The text is grounded in context, explaining how Public Law operates in practice, and it thoroughly covers the spectrum of Constitutional Law, Human Rights and Administrative Law. Integrated pedagogic features ease navigation of the text and reinforce key points. These include Public Law in Context, Recent Developments, Public Law in Practice, Practical Application and Academic Debate, and Public Law is also supported by online Multiple Choice Questions. Public Law is essential reading for modules on public law and constitutional and administrative law on LLB degrees and conversion courses"--